PROFESSIONAL ORIENTATION WORK WITH STUDENTS OF THE CENTER FOR PRE-PROFESSIONAL TRAINING AND GIFTED STUDENTS OF ESIED OF NAU IN WARTIME - Petrovska, Tetiana (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
The article highlights the actual issue of career guidance work with school youth during wartime.The importance of career orientation for future applicants is revealed.